Coverage- and temperature-induced self-metalation of tetraphenyltransdibenzoporphyrin on Cu(111) - Shaker, Majid; Muth, Maximilian; Steffen, Julien; Ceccatto Dos Santos, Alisson; Jaekel, Simon; Adhikari, Rajan; Gazetas, Pascal; Oleszak, Christoph; de Siervo, Abner; Jux, Norbert; Görling, Andreas; Lytken, Ole; et al. (Journal of Physics: Condensed Matter, 2025)
We have investigated the adsorption and self-metalation of free-base tetraphenyltransdibenzoporphyrin (2H-TPtdBP) on Cu(111) as a function of coverage and temperature using scanning tunneling microscopy, x-ray photoelectron spectroscopy, temperature programmed desorption, and density-functional theory calculations. At low coverages (<0.16 molecules nm-2), we observe isolated individual molecules with an inverted conformation and no self-metalation up to 363 K. At higher coverages, both the formation of ordered islands and self-metalation are observed over time already at room temperature, and accelerate upon heating to 363 K. At 423 K, complete self-metalation occurs for all coverages up to the completed first layer. By comparing our results for 2H-TPtdBP to the existing literature on other tetraphenyl-based porphyrins, we demonstrate how adsorption and self-metalation can be tailored by the choice of substituents.
CRIS-Team Scopus Importer:2025-02-04
Keywords: DFT; porphyrins; self-assembly; self-metalation; STM; TPD; XPS